Zakat on Crypto Assets and Sharia Financial Inclusion: A Comparative Fiqh al-Muamalah Analysis in Indonesia and Malaysia - Irpan Helmi; Mery Maulin (Program Pascasarjana IAIN Langsa, 2025)
The rapid expansion of digital financial technology has increasingly influenced the landscape of Islamic social finance, including the emerging discussion on the use of crypto assets for zakat payments. While cryptocurrencies such as Bitcoin are widely used in global financial transactions, their status as zakatable wealth (māl zakawī) remains contested among Muslim scholars and regulators. Existing studies have largely focused on the legality of cryptocurrency in Islamic finance, yet limited attention has been given to its practical implications for zakat governance and institutional regulation. This study therefore examines the permissibility of crypto assets as objects of zakat from the perspective of fiqh al-muamalah and compares the regulatory approaches adopted in Indonesia and Malaysia. This research employs a qualitative library-based method through the analysis of classical and contemporary Islamic legal literature, relevant fatwas, and regulatory frameworks related to cryptocurrency and zakat administration. A comparative approach is used to explore differences in institutional responses between the two countries. The findings indicate that Malaysia has adopted a more adaptive regulatory approach by facilitating crypto-based zakat payments through authorised institutions such as Lembaga Zakat Selangor (LZS) and Pusat Pungutan Zakat (PPZ). In contrast, Indonesia maintains a more cautious stance due to ongoing scholarly debates and regulatory uncertainties surrounding the classification of crypto assets. From an Islamic legal perspective, crypto assets may be regarded as zakatable wealth when they fulfil the criteria of māl mutaqawwim, including lawful ownership, recognised economic value, and compliance with Sharia principles. These findings highlight the potential role of blockchain technology in improving transparency, accountability, and public trust in zakat management while expanding financial inclusion among digitally engaged Muslim communities.